Alternatives to the use of antibiotics for laying hens in growing phase - Tfaile, S. M. C.; Moraes, J. E. de; Budino, F. E. L.; Soares, D. F.; Sitanaka, N. Y.; Duarte, K. M. R.; Kakimoto, S. K.; Reis, T. L.; Amoroso, L. [UNESP]; Pizzolante, C. C. (South African Journal Of Animal Sciences, 2020)
This study evaluated the performance, immune response to vaccination, digestive organs, intestinal histomorphometry, and microbiological development in the diet and litter of Isa Brown strains at growing receiving phase alternative additives in the place of antibiotics. Four treatments were arrayed in a completely randomized design: T1) Basal diet without antibiotics, T2) Basal diet with antibiotics, T3) Basal diet with probiotics, and T4) Basal diet without antibiotics and water modified by a photoelectron generator. There were six replications of eight birds each and thus a total of 192 birds. Performance was evaluated for eight weeks and during this period blood samples were collected at 9, 12 and 15 weeks of age for serological evaluation. At the end of the experimental period, 24 birds were euthanized, collecting the intestinal tract and later performing histomorphometry. Microbiological analyses were performed in the experimental diets and in the material of the litter of the boxes. The results obtained were analyzed by analysis of variance and the contrast between treatment means when significant by Tukey's test. The results indicate that the replacement of antibiotics with T3 or T4 did not interfere negatively (P >0.05) in the performance of the birds, immunological response, viscera analyses and intestinal histomorphometry. In addition, use of T3 and T4 might lead to more rapid decomposition of excreta and reduce antibiotic residue in the soil when the litter is used in crop production.
Keywords: dileka; Gallus domesticus; histomorphometry; laying hens; probiotics; serum biochemistry; water